Norcantharidin ameliorates estrogen deficient-mediated bone loss by attenuating the activation of extracellular signal-regulated kinase/ROS/NLRP3 inflammasome signaling - Yang, Guang; Xu, Huikang; Yao, Minjun; Yan, Shigui; Wu, Mengrui; Zhou, Chenhe (Frontiers in Pharmacology, 2022)
Osteoporosis, characterized by reduced bone mass, aberrant bone architecture, and elevated bone fragility, is driven by a disruption of bone homeostasis between bone resorption and bone formation. However, up to now, no drugs are perfect for osteoporosis treatment due to different defects. In this study, we demonstrated that norcantharidin (NCTD) could inhibit osteoclast formation and bone resorption by attenuating the ERK, ROS and NLRP3 inflammasomes pathways in vitro. Moreover, our in vivo study further confirms its preventive effects on estrogen-deficiency bone loss by inhibiting osteoclast formation and functions. Therefore, we could conclude that NCTD might be a potential candidates for the prevention and treatment of osteoporosis.